2018
DOI: 10.1371/journal.pone.0195753
|View full text |Cite
|
Sign up to set email alerts
|

Green tea extracts ameliorate high-fat diet–induced muscle atrophy in senescence-accelerated mouse prone-8 mice

Abstract: Muscle atrophy (loss of skeletal muscle mass) causes progressive deterioration of skeletal function. Recently, excessive intake of fats was suggested to induce insulin resistance, followed by muscle atrophy. Green tea extracts (GTEs), which contain polyphenols such as epigallocatechin gallate, have beneficial effects on obesity, hyperglycemia, and insulin resistance, but their effects against muscle atrophy are still unclear. Here, we found that GTEs prevented high-fat (HF) diet–induced muscle weight loss in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…For example, gosha-jinki-gan alleviated skeletal muscle atrophy through Akt/FoxO4/MuRF1-and AMPK/PGC-1α-associated mitochondrial dysfunction in SAMP8 mice [146]. Furthermore, high-fat-diet-fed SAMP8 mice exhibited susceptibility to aging-related muscle wasting, and the muscle weight was decreased by 15.3% at 6 months of age compared with that at 2 months of age [147]. Several observations suggested that the use of SAMP strains is cost-effective for sarcopenia research.…”
Section: Senescence-accelerated Mouse (Sam)mentioning
confidence: 97%
See 1 more Smart Citation
“…For example, gosha-jinki-gan alleviated skeletal muscle atrophy through Akt/FoxO4/MuRF1-and AMPK/PGC-1α-associated mitochondrial dysfunction in SAMP8 mice [146]. Furthermore, high-fat-diet-fed SAMP8 mice exhibited susceptibility to aging-related muscle wasting, and the muscle weight was decreased by 15.3% at 6 months of age compared with that at 2 months of age [147]. Several observations suggested that the use of SAMP strains is cost-effective for sarcopenia research.…”
Section: Senescence-accelerated Mouse (Sam)mentioning
confidence: 97%
“…Guo et al showed that the number of type II muscle fibers, which are predominant in gastrocnemius muscles, reached a peak at 7 months of age and then declined gradually in SAMP8 mice [ 145 ]. Consequently, SAMP8 mice have been used to investigate novel sarcopenia therapeutics and assess their efficacy [ 120 , 146 , 147 ]. For example, gosha-jinki-gan alleviated skeletal muscle atrophy through Akt/FoxO4/MuRF1- and AMPK/PGC-1α-associated mitochondrial dysfunction in SAMP8 mice [ 146 ].…”
Section: Models For Studying Sarcopeniamentioning
confidence: 99%
“…The animal experiments described in this study were carried out simultaneously with those described in our recent publication [19]. In brief, male SAMR1 (Number of samples, N = 24) and SAMP8 ( N = 56) mice were obtained from Japan SLC, Inc. (Hamamatsu, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Calorie-based average daily amount of food intake per mouse (kcal/mouse/day) did not differ significantly among the groups and was 17.00 (SAMR1; Cont), 17.06 (SAMP8; Cont), 19.06 (SAMP8; HF), and 18.13 (SAMP8; HFGT). Although no significant difference in body weight was observed among any groups of mice at 6 months of age, the HF group of SAMP8 mice had insulin resistance, as assessed by homeostasis model assessment of insulin resistance (HOMA-IR) [19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation